RAPUNZEL SYNDROME - Bashir, Eitezaz Ahmed; Samiullah, Samiullah; Sadiq, Muhammad Attique; Yusuf, Omamah; Karim, Khan (Journal of Ayub Medical College Abbottabad, 2010)
A trichobezoar may be confined to the stomach or unusually it may extend from stomach to the small intestine or beyond when it is labelled as Rapunzel syndrome. Bezoars are concretions in the gastrointestinal tract that increase in size by continuous accumulation of non-absorbable food or fibre. Most bezoars in children are trichobezoars from swallowed hair. Repunzal syndrome is an uncommon condition in children with less than 40 cases reported. We present a case of an 8 year old girl with Rapunzel syndrome. She presented with vague abdominal pain and epigastric fullness of one year duration. On investigation she was found to have a trichobezoar. At laparotomy a large dark foul smelling trichobezoar that occupied the stomach, duodenum and proximal jejunum was removed via gastrostomy. Keywords: Trichobezoar, abdominal mass, Rapunzel syndrome